PERSPEKTIF PEDAGANG TERHADAP EFEK SEDEKAH MELALUI BERKAH DALAM MEMUDAHKAN PEROLEHAN REZEKI - Dini Fakhira Bahari; Marlya Fatira AK (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
This article discussing about the perspective of traders on how the effects of Alms through Friday blessings in facilitating the acquisition of sustenance. The analytical technique used is simple linear analysis with quantitative methods. The data collection technique was carried out using questionnaires which were distributed to 30 respondents by visiting the respondents' selling locations. The results showed that Alms had a significant effect on the ease of obtaining sustenance, as evidenced by the Tcount value of 6.901 and the significance value of 0.000.